FINITE ELEMENT ANALYSIS OF THE STRESS-STRAIN STATE OF 3D COMPUTER GENERATED IMAGING OF REVERSE TOTAL SHOULDER ENDOPROSTHESES - Korzh, Mykola; Makarov, Vasyl; Chilik, Marcin; Zdanevych, Serhii; Smoliar, Maksym (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective. To conduct a finite element analysis of the stress-strain state (STS) of the elements of the shoulder joint after implantation reverse shoulder endoprostheses. Material and methods. After 3Dscanning of the composite model of the scapula and humerus, geometric models of the shoulder joint were built in the SolidWorks 2019 SP 1.0 program, followed by mathematical modeling and FEA. For the comparative analysis of the STS of the «bone – reverse endoprosthesis» s ystem, t hree-dimensional m odels o f two types of reverse shoulder endoprostheses were created, which were then transformed into a finite-element model and implanted into the developed three-dimensional mathematical model of the shoulder joint without cement. The STS calculations of the elements of endoprostheses were carried out for two positions: abduction 90° and flexion 90° with a load of 5 kg. Results. Compared to the healthy shoulder joint, models with reverse shoulder endoprosthesis have significantly different contact stresses and contact areas. It was established that the maximum stress in the details of the contact parts of the endoprosthesis when retracted at an angle of 90° did not exceed +1.78 MPa, when bending +5.8 MPa. The maximum stresses on the liner during shoulder abduction are +8.6 MPa, the minimum –7.38 MPa, during flexion +2.3 MPa and –2.45 MPa, respectively. It has been proven that the contact areas of the hemisphere and inserts of both reverse endoprostheses during abduction and flexion of the limb by 90° are significantly larger (573 mm2 vs. 1809–2081 mm2) when compared with a healthy shoulder joint, while changes in the area between the endoprostheses are insignificant and equal to 2...3 %. Conclusions. Analysis of the STS load of elements of reverse shoulder endoprosthesis showed that the greatest stresses occur in the contact zones. It has been proven that the maximum stresses on the contact structures of endoprostheses are less than on the head of a healthy joint, but the contact area during implantation of a reversible endoprosthesis of the shoulder joint increases significantly (more than 3 times).